2004
DOI: 10.1111/j.1523-1755.2004.66004.x
|View full text |Cite
|
Sign up to set email alerts
|

AGEs activate mesangial TGF-β–Smad signaling via an angiotensin II type I receptor interaction

Abstract: The present study suggests that AGE-RAGE-mediated ROS generation activates TGF-beta-Smad signaling and subsequently induces mesangial cell hypertrophy and fibronectin synthesis by autocrine production of Ang II. This pathway may provide an important link between metabolic and haemodynamic factors in promoting the development and progression of diabetic nephropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
156
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 210 publications
(163 citation statements)
references
References 68 publications
6
156
0
1
Order By: Relevance
“…Preparation of antiserum directed against RAGE Antiserum directed against human RAGE for neutralising assays was prepared as described previously [6].…”
Section: Methodsmentioning
confidence: 99%
“…Preparation of antiserum directed against RAGE Antiserum directed against human RAGE for neutralising assays was prepared as described previously [6].…”
Section: Methodsmentioning
confidence: 99%
“…Intracellular ROS Production-Intracellular ROS production by human RPE cells in response to TNF-α, IL-1β, or IFN-γ treatment was measured by a cell-based fluorometric assay based on deacetylation and oxidation of non-fluorescent reduced CM-H 2 DCFDA (Molecular Probes) into fluorescent CM-DCF. The reliability and specificity of the probe have been established in various cells including cultured human RPE cells (Deshpande et al, 2000;Nishikawa et al, 2000;Touyz et al, 2001;Yamagishi et al, 2001;Higgins et al, 2003;Li et al, 2003;Fukami et al, 2004;Hermann et al, 2004;Hwang et al, 2004;Kannan et al, 2004;Shanker et al, 2004;Kim et al, 2005). RPE cells were seeded into 96-well plates pre-coated with poly-D-lysine (Sigma-Aldrich) and cultured for 1 day or 7days.…”
Section: Measurement Of Reactive Oxygen Species Production By Rpe Cellsmentioning
confidence: 99%
“…AGE and TGF-b products have been implicated in the pathogenesis of human diabetic nephropathy [14,15]. Recently, we reported that KK-A y mice exhibited type 2 diabetes and diabetic nephropathy from 8 to 20 weeks of age [11].…”
Section: Discussionmentioning
confidence: 99%